2015
DOI: 10.1179/1743132815y.0000000033
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss: indication of brain damage and effect of combined normobaric oxygen and ethanol therapy after stroke

Abstract: Degree of weight loss after stroke is largely associated with severity of infarction as well as damage reduction after treatment administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Protein levels of PKC-δ, p-Akt, Caspase-3, Bax, and Bcl-XL were detected by western blotting. Brain tissues containing the frontoparietal cortex and dorsolateral striatum were processed as described previously [34] and incubated with primary antibodies (polyclonal rabbit anti-PKC-δ at 1:5000, Santa Cruz Biotechnology, Santa Cruz, CA, USA; polyclonal rabbit anti-phospho-Akt 1:1000, Cell Signaling Technology, Danvers, MA, USA; rabbit polyclonal anti-caspase-3 antibody, 1:1000, Santa Cruz Biotechnology, Santa Cruz, CA, USA; rabbit polyclonal anti-cleaved caspase-3 antibody, 1:5000, Santa Cruz Biotechnology, Santa Cruz, CA, USA; rabbit polyclonal anti-BAX antibody, 1:500, Santa Cruz Biotechnology, Santa Cruz, CA, USA; mouse monoclonal anti-Bcl-XL, 1:200, Santa Cruz Biotechnology, Santa Cruz, CA, USA) at 4 • C. Western blot images were analyzed by an image analysis program (ImageJ 1.42, National Institutes of Health, Bethesda, MD, USA) to quantify protein expression in terms of relative image density.…”
Section: Western Blottingmentioning
confidence: 99%
“…Protein levels of PKC-δ, p-Akt, Caspase-3, Bax, and Bcl-XL were detected by western blotting. Brain tissues containing the frontoparietal cortex and dorsolateral striatum were processed as described previously [34] and incubated with primary antibodies (polyclonal rabbit anti-PKC-δ at 1:5000, Santa Cruz Biotechnology, Santa Cruz, CA, USA; polyclonal rabbit anti-phospho-Akt 1:1000, Cell Signaling Technology, Danvers, MA, USA; rabbit polyclonal anti-caspase-3 antibody, 1:1000, Santa Cruz Biotechnology, Santa Cruz, CA, USA; rabbit polyclonal anti-cleaved caspase-3 antibody, 1:5000, Santa Cruz Biotechnology, Santa Cruz, CA, USA; rabbit polyclonal anti-BAX antibody, 1:500, Santa Cruz Biotechnology, Santa Cruz, CA, USA; mouse monoclonal anti-Bcl-XL, 1:200, Santa Cruz Biotechnology, Santa Cruz, CA, USA) at 4 • C. Western blot images were analyzed by an image analysis program (ImageJ 1.42, National Institutes of Health, Bethesda, MD, USA) to quantify protein expression in terms of relative image density.…”
Section: Western Blottingmentioning
confidence: 99%
“…The reason for this dramatic and prolonged weight loss after stroke is unclear and could involve several mechanisms, including reduced food intake and/or raised energy expenditure, possibly via the action of inflammatory mediators. Acute weight loss after experimental stroke can correlate positively with ischaemic damage [30,58], although this correlation is not always observed [18]. Here, the degree of weight loss over 49 days did not directly correlate with initial damage at 48 h, suggesting that post-stroke weight loss may be caused by factors secondary to the initial injury, and develop during recovery.…”
Section: Discussionmentioning
confidence: 77%
“…Weight loss has occurred after CIRI in both NG and T1DM rats so that T1DM rats are lighter than NG rats at both baseline and 24 h after 75‐min ischemia. Studies have shown a positive correlation between infarct volume and weight loss after acute stroke (Cai et al., 2015 ). A greater weight loss in T1DM rats is probably related to the increased severity of CIRI when compared to NG rats.…”
Section: Discussionmentioning
confidence: 99%